Urgensi Pemasaran Usaha Mikro Kecil dan Menengah (UMKM) Dalam Meningkatkan Perekonomian Daerah Berbasis Ekonomi Syariah - Arfah Arfah (ISLAMIC BUSINESS and FINANCE, 2022)
Marketing UMKM based on sharia economics aims to improve marketing, strengthen the regional economy, and anticipate the problems of UMKM in the area where there has been a decline in UMKM in the region, especially Indragiri Hulu Regency in the last three years in 2018-2019 and 2020. As a result of the COVID-19 pandemic, it is a particular concern for local governments to bring back UMKM so that the economic crisis is not sustainable and has an impact on unemployment and poverty in the regions; it is necessary to have a new paradigm to restore UMKM with a marketing strategy based on sharia economics. The research method used is descriptive qualitative by using primary data. Data analysis conducted is based on the phenomenon that occurs. The result of the study shows that UMKM marketing in increasing sales uses the 4P marketing mix, namely the product mix (Product), price mix (Price), distribution mix (Place), promotion mix (Promotion), Place, and Service targets. There has not been an official UMKM local entrepreneur and market in Indragiri Hulu Regency with a sharia economic-based marketing system, except Islamic Bank Financial Institutions and Sharia Non-Banking Financial Institutions.Keywords: UMKM Marketing, Regional Economy, Sharia economic